Analisis Faktor Penentu Kepuasan Mahasiswa dan Dosen Terhadap Kualitas Pelayanan Jurusan Perikanan Fakultas Peternakan Sebelum dan Masa Pandemi Covid 19 - Lisna Lisna; Nelwida Nelwida; Firmansyah Firmansyah; Afriani Afriani; Nurhayati Nurhayati; Haris Lukman (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to determine the difference in the level of student and lecturer satisfaction with the service quality of the Department of Fisheries, Faculty of Animal Husbandry before and during the COVID-19 pandemic, and the factors that determine the level of satisfaction. This research is a qualitative descriptive study using Stratified Random Sampling as a sampling technique consisting of Strata I students from the Department of Fisheries and Strata II as teaching lecturers from the Department of Fisheries. The sample size was determined using the Krejcie and Morgan formula. The research instrument used a Likert Scale questionnaire (Summated Rating Scale) which was tested with validity and reliability tests. To analyze the determinants used Path Analysis. There was no difference in the level of student satisfaction with the service quality of the Department of Fisheries, Faculty of Animal Husbandry before and during the Covid 19 pandemic. The level of student satisfaction with the service quality of the Department of Fisheries before the Covid 19 pandemic was in the Less category (C score) with a score of 73.69, while during the The Covid 19 pandemic is in the poor category (C value) with a score of 73.15. The biggest determining factor for the level of student satisfaction with the service quality of the Department of Fisheries, Faculty of Animal Husbandry before the Covid 19 pandemic was Assurance. while during the Covid 19 pandemic is Reliability.